Argamassas do grupo escolar Augusto Severo/RN: caracterização e incidência de manifestações patológicas - Sousa, Adla Kellen Dionisio (2014)
The search for cultural heritage preservation should be a constant, in order to minimize the lost of historical and cultural identity of a country. As part of this cultural heritage, highlights the importance of historical buildings. For the principles of restoration are met its important to know the state of conservation and the existing materials. Given the above, this work aims to study the pathological manifestations of the mortar coating from the Grupo Escolar Augusto Severo. For this, was conducted historical survey of the building, on-site visits with visual observation, collecting samples of mortar coating and characterization through visual and laboratory analysis, XRF, XRD, TG/DTG, OM and SEM-EDS. From the observations, pathological manifestations were found as: cracks, detachment of the coating, dirt, use of inappropriate material basis of cement, efflorescence, mold and mildew and also incompatible material base of cement. It was found that the pathological manifestations were intensified due to lack of coverage in some spots and especially the abandonment of the building, that many years does not have restoration or any other type of preventive and corrective maintenance. The results of laboratory tests indicated that the mortars studied are based on lime, with calcitic nature, and siliceous aggregate, with the presence of clay in two samples. From the samples collected, two are composed of lime, sand and clay and two by lime and sand. In this regard, it is important to conduct periodic inspections and maintenance, as well as carrying out restoration with use of material compatible with the original